A Case of Human Lassa Virus Infection With Robust Acute T-Cell Activation and Long-Term Virus-Specific T-Cell Responses. (22nd June 2017) - McElroy, Anita K.; Akondy, Rama S.; Harmon, Jessica R.; Ellebedy, Ali H.; Cannon, Deborah; Klena, John D.; Sidney, John; Sette, Alessandro; Mehta, Aneesh K.; Kraft, Colleen S.; Lyon, Marshall G.; Varkey, Jay B.; et al.
Summary: A detailed characterization of the human immune response to Lassa virus infection reveals an association between virus clearance and interferon α, robust B- and T-cell activation during acute infection, and the generation of polyfunctional Lassa-specific T-cell responses. Abstract: A nurse who acquired Lassa virus infection in Togo in the spring of 2016 was repatriated to the United States for care at Emory University Hospital. Serial sampling from this patient permitted the characterization of several aspects of the innate and cellular immune responses to Lassa virus. Although most of the immune responses correlated with the kinetics of viremia resolution, the CD8 T-cell response was of surprisingly high magnitude and prolonged duration, implying prolonged presentation of viral antigens. Indeed, long after viremia resolution, there was persistent viral RNA detected in the semen of the patient, accompanied by epididymitis, suggesting the male reproductive tract as 1 site of antigen persistence. Consistent with the magnitude of acute T-cell responses, the patient ultimately developed long-term, polyfunctional memory T-cell responses to Lassa virus.